Nikah Misyᾱr, : Perspektif Fatwa Ulama’, Gender Dan Hukum Keluarga Islam Di Indonesia - M. Halilurrahman; Aisyah Dana Luwihta (JURISY: Jurnal Ilmiah Syariah, 2023)
Abstract : The phenomenon of misyᾱr marriage raises debate among contemporary scholars. Contemporary scholars issue fatwas that are contradictory to one another by looking at different points of view. From the fatwas that have been issued by contemporary ulemas about misyᾱr marriages, the issue of protection and rights of women (wives) and the goals of shari'ah (maqᾱṣid al-sharī'ah) in misyᾱr marriages are the main reasons that are being debated among contemporary ulema'. This research uses a qualitative approach with a type of library research. The collection of legal material is carried out by examining documents, namely the fatwa of each ulema. Legal material analysis techniques include content analysis and critical analysis of the fatwa in terms of gender and maqᾱṣid al-sharī'ah perspectives. The results of the study show that: (1) There are two groups of contemporary 'ulama', namely 'ulama' who allow misyᾱr marriage, namely Yūsuf al-Qardhᾱwi and Wahbah Zuhailī and 'ulama' who prohibit misyᾱr marriage, namely 'Abd al-'Aziz bin al-Bᾱz and 'Abd al-'Aziz bin al-Bᾱz and ' Umar Sulaimᾱn al-Aṣqar. This difference is due to: First, differences in manhaj in establishing law. Second, the difference in determining the criteria for the validity of the marriage. Third, differences in understanding whether or not socialization is mandatory in a marriage. (2) Between the contemporary ulama' fatwa which allows and prohibits misyᾱr marriage when viewed from a gender perspective, the ulama' fatwa which prohibits it is more in accordance with the concept of gender on the basis of protecting women's rights more.